Respiratory Practices to Prevent or Treat Evolving Bronchopulmonary Dysplasia: A European Survey - Van De Loo; Moniek; Onland, Wes; Hutten, Jeroen; Lavizzari, Anna; Heiring, Christian; Aldecoa-Bilbao, Victoria; Ehrhardt, Harald; Cetinkaya, Merih; Szczapa, Tomasz; Sartorius, Victor; Rocha, Gustavo; et al. (Elsevier, 2026)
Objective
To investigate respiratory practices to prevent or treat evolving bronchopulmonary dysplasia in neonatal intensive care units (NICUs) across Europe.
Study design
Between March and July 2024, a web-based survey was sent to European NICUs caring for infants born preterm with gestational age <28 weeks.
Results
We received replies from 447 of 721 (62%) NICUs across 24 European countries. Almost 16% of NICUs routinely intubate at birth, especially if the gestational age is <24 weeks. During transition most NICUs use continuous positive airway pressure ≥5 cmH2O and start with an FiO2 0.3. Volume-targeted ventilation is the primary ventilation mode in 60% of the NICUs. Permissive hypercapnia is a common practice. Higher SpO2 target limits have been adopted, although alarm settings vary across NICUs. Caffeine is routinely started (96%). Surfactant is used in all NICUs, mostly rescue (74%) via less invasive administration (81%). Prophylactic inhaled nitric oxide is not used. Treatment of patent ductus arteriosus varies; half of NICUs pharmacologically treat patent ductus arteriosus early, based on echocardiographic findings. Ureaplasma screening is done in 22% of NICUs. Most (97%) NICUs use postnatal corticosteroids, with dexamethasone being the preferred drug (65%) and starting 2-3 weeks after birth. Only 5% use corticosteroids prophylactically. After 2-3 weeks, diuretics are used frequently, inhaled corticosteroids/bronchodilators to a much lesser extent.
Conclusions
This large survey shows considerable practice variation in preventing and treating evolving bronchopulmonary dysplasia across Europe, especially for interventions with limited evidence.